SISTEM INFORMASI PENDAFTARAN SUKARELAWAN BERBASIS WEB PADA KOMUNITAS TEMAN BINCANG - Vera Felia; Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The Volunteer Registration Application for the Teman Bincang Community is a web-based application that is designed to make it easier for users to apply as volunteers in the Teman Bincang Community for specific positions. Teman Bincang is a community that provides online psychological services related to mental health education. The community was established in February 2020, and the people working there are volunteers with specific positions. The information on open positions for volunteering is still limited and currently only available through posts on the Instagram application. The application process also still uses Google Forms with limited features, which means that the information received by the applicants is still limited. The main objective of this thesis is to create a website that will help users to register as volunteers for specific positions in Teman Bincang, which consists of various sections and pages. The recruiters will also be able to view the list of volunteer applicants and other data on the website. The development of this web-based system uses PHP programming language, Bootstrap framework, and MySQL database. The System Development Life Cycle (SDLC) Waterfall methodology is used for the development process, and the testing is done with Black Box Testing and User Acceptance Testing methods. The conclusion of this thesis is that the application runs well in terms of appearance and functionality, without any bugs or errors. Additionally, the application is very user-friendly, easy to understand and easy to use by the user.